Penggunaan Teknologi Artificial Intelligence (AI) Terhadap Pendidikan Bisnis (Sytematic Literature Review Analysis) - Eko Mety Setyowati; Rahmawati Rahmawati; Ahmad Happy Nashrullah; Syafrozi Haqi; Ludi Wishnu Wardana; Bagus Shandy Narmaditya (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to systematically analyze the current literature on the role of Artificial Intelligence (AI) in business education, especially in the context of entrepreneurship. Through a Systematic Literature Review (SLR) approach to scientific articles published between 2022 and 2025 from various academic databases such as Elsevier, Emerald, and Google Scholar, this study identifies and synthesizes ten key roles of AI in transforming business education. These roles include improving the ability to identify business opportunities, facilitating the development of innovative ideas, supporting strategic business planning, personalizing learning experiences, providing personalized guidance and mentoring, enabling realistic business simulations, accelerating the validation of business ideas, supporting the development of business incubators, increasing the efficiency of assignment assessments, and encouraging ethical and sustainable thinking. The results of the literature analysis show that AI offers significant potential in improving the efficiency, effectiveness, and quality of entrepreneurship learning. However, successful implementation of AI requires a comprehensive transformation of the educational paradigm, including curriculum updates, training of educators, and attention to ethical, regulatory, and cultural issues. This study provides a clear and structured overview of the contribution of AI in business education, identifies challenges and opportunities, and formulates recommendations for inclusive and sustainable AI integration.